ETR 300 : Idaman Exclusive Furniture / Faizal Shahrin Kamal Farid ...[et al.] - Kamal Farid, Faizal Shahrin; Mustafa, Azrina; Nasarudin, Muzaffar Ariff; Hasan, Hazimah; Ishak, Emilia (2000)
Jdaman is a professionally managed partnership finn consisting of five members who carry out a business in exclusive furniture. The firm is under the leadership of a General Manager, Mr. Faizal Shahrin Kamal Farid. Ms Hazimah Hassan as a Financial Manager will manage the budget wisely. As a Production Manager, Mr. Muzaffar Ariff believes in quality as well as design excellence in our products. The philosophies· of taking into account our client's needs helps the management to focus into niche markets regionally. The management outlook is progressive and the finn is currently expanding our product range as well as market channel and that task will be done by Ms Imilia Ishak. The marketing department is headed by Ms. Azrina Mustafa and she will spearhead the marketing efforts of the company. We choose the name Idaman because it means desire, it is in line with our mission that is to fulfill customers desire in having nice exclusive atmosphere in their home. The word Idaman also is easy to pronounces.